2016
DOI: 10.1186/s41235-016-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

On the learning benefits of confidence-weighted testing

Abstract: Taking multiple-choice practice tests with competitive incorrect alternatives can enhance performance on related but different questions appearing on a later cued-recall test (Little et al., Psychol Sci 23:1337–1344, 2012). This benefit of multiple-choice testing, which does not occur when the practice test is a cued-recall test, appears attributable to participants attempting to retrieve not only why the correct alternative is correct but also why the other alternatives are incorrect. The present research was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Confidence-weighted testing improves learning of the material and increases learners’ knowledge of educational content tied to both correct and incorrect answer choices for each question. 10 , 11 Additionally, it allows for individualized feedback to optimize the learner’s time and knowledge acquisition. For example, when a learner confidently answers a question correctly, no additional instruction or corrective feedback is provided during the module because it would not improve learning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Confidence-weighted testing improves learning of the material and increases learners’ knowledge of educational content tied to both correct and incorrect answer choices for each question. 10 , 11 Additionally, it allows for individualized feedback to optimize the learner’s time and knowledge acquisition. For example, when a learner confidently answers a question correctly, no additional instruction or corrective feedback is provided during the module because it would not improve learning.…”
Section: Methodsmentioning
confidence: 99%
“…Although other studies have demonstrated the value of eLearning in pediatric sepsis, 7 this report aims to describe our experience applying confidence-weighted testing to enhance learning. 10 , 11 To the extent that our initiative was successful, the principles we used in developing and evaluating our intervention could be incorporated in future education components of other QI initiatives to optimize learning and identify specific areas of local misinformation that could inform subsequent improvement efforts.…”
Section: Introductionmentioning
confidence: 99%
“…However, with repeated use of CA over time, calibration tends to improve (Gardner-Medwin & Curtin, 2007). It has been found that CA, often implemented in a multiple-choice context, can encourage self-checking, self-explanation and higher-level reasoning (Gardner-Medwin & Curtin, 2007;Sparck et al, 2016), and improve test validity by reducing gender bias (Hassmén & Hunt, 1994). Consequently, it has been suggested (Foster, 2016(Foster, , 2017Foster et al, 2021) that CA might have considerable potential benefits for formative assessment in the school mathematics classroom.…”
Section: Uses Of Confidence Assessmentmentioning
confidence: 99%
“…We cannot completely rule out this possibility; however, the fact that confidence scores ranged across all of the emojis is evidence that large numbers of students were willing to register low confidence. One way in which to collect confidence measures with higher validity could be to implement confidenceweighted assessment, in which the student's mark is increased when the student expresses high confidence and is correct but is decreased when the student expresses high confidence but is incorrect (see Dirkzwager, 2003;Foster, 2016Foster, , 2021Rosewell, 2011;Sparck et al, 2016). Such an approach is intended over time to incentivise truthful confidence ratings and is particularly easy to implement in a multiple-choice model, where students can be asked to allocate, say, 100 marks across the four options A-D.…”
Section: Limitationsmentioning
confidence: 99%